The Association Between Parenting and Parental Communication with Temper Tantrums in Preschool Children - Tambunan, Dior; Sansuwito, Tukimin (Holistic Nursing Plus, 2024)
Background: Temper tantrums are a behavior that often occurs in preschool children. This behavior is characterized by excessive emotional expression and uncontrolled behavior, arising from the children’s frustration and anger. Purpose: To identify whether there is a relationship between parenting and parental communication with temper tantrums in preschool children. Methods: The research design used in this study is cross sectional. This research was conducted in year of 2023 with a total of 65 respondents using a total sample technique. The instruments in this study were questionnaires on parenting, parental communication, and temper tantrums which were adopted from previous research and had been tested for validity and reality. The data analysis used was the Spearman correlation test because the data was not normally distributed. Results: The results of this study showed that there is no significant relationship between parenting and parental communication with temper tantrums in preschool children. Conclusions: The important role of parents in providing good parenting in shaping preschool children's behavior. The better the parenting and parental communication, the better the handling of temper tantrums in preschool children. It is recommended for future researchers to add variables of emotional intelligence and mother's level of knowledge regarding temper tantrums in preschool children.